Direct Aggression and the Balance between Status and Affection Goals in Adolescence - Sijtsema J.; Lindenberg S.; Ojanen T.; Salmivalli C. (Springer New York LLC, 2025)
Previous studies have shown that status goals motivate direct forms of interpersonal aggression. However, status goals have been studied mostly in isolation from affection goals. It is theorized that the means by which status and affection goals are satisfied change during adolescence, which can affect aggression. This is tested in a pooled sample of (pre)adolescents (N = 1536; 49% girls; ages 10–15), by examining associations between status goals and direct aggression and the moderating role of affection goals. As hypothesized, with increasing age, status goals were more strongly associated with direct aggression. Moreover, for older adolescents, status goals were only associated with aggression when affection goals were weak. These findings support the changing relationship between status goals and direct aggression during adolescence.